Risks for connectivity providers on the increase - any opportunities? - Derk Oldenburg (International Telecommunications Society (ITS), 2024)
According to the January 2024 WEF Global Risks Report, concerns about the risks related to cyber insecurity, misinformation and adverse outcomes of AI are at the top of minds in the coming two years, followed by extreme weather events and societal polarization. In the coming decade, the effects of climate change are projected to have an even more serious impact. What these risk trends mean to network operators / digital connectivity providers and how they can achieve a better level of resilience, is the object of important and timely studies. A broad range of vulnerabilities have to be addressed in the coming years. But how about the other side of the coin? Are there opportunities for digital infrastructure providers in the rather bleak future the WEF report (and others) sketches? This policy article aims to stimulate a process of creative thinking, looking for opportunities related to five specific risk trends.
Keywords: 330